Typification of cocoa-producing farms (Theobroma cacao L.) in Montes de María and La Mojana, Colombia - Martínez-Reina, Antonio María (2023)
Introduction. The cocoa production system is an integral part of Colombian agriculture in the subregions of Montes de María and La Mojana in the department of Sucre. There is currently no evidence in the literature regarding acharacterization and typification of the study of this production system. Objective. To analyze the socio-economic and technological aspects of cocoa cultivation in the Montes de María and La Mojana subregions and define homogeneousgroups of producers sharing similar characteristics that serve as recommendation domains. Materials and methods. Surveys were designed and conducted among farmers in the Montes de María and La Mojana region during 2019. Twenty-two farmers were selected through deterministic sampling. The analysis involved the typification of farmersusing the distance method and Ward’s hierarchical clustering. Results. Three groups of farmers were identified. Group GI exhibited a low technological level, with farmers having incomplete primary education and low yields (420 kg ha-1). Group GII consisted of farmers with incomplete secondary education, achieving higher yields than GI (491 kg ha-1) and incorporating practices like formation and maintenance pruning. Group GIII had a higher level of education, used technological options such as improved planting materials and crop management techniques, and obtained the highest yields among all farmers (550 kg ha-1). Conclusion. The typified farms displayed differences among the groups, concluding that group G3 achieved the highest yields per hectare, attributed to the adoption of new technologies.